Risk Factors for Preterm Birth: A Comprehensive Review of Current Evidence - Piekarska, Julia; Solarz, Justyna Maria; Wawrzyńców, Jakub Tomasz; Cyrkler, Weronika; Robak, Jakub; Telega, Stanisław; Bollin, Paweł; Szymczak, Urszula; Lachór, Wojciech Wiesław; Solarz , Monika Barbara (Quality in Sport, 2025)
Preterm birth, defined as the termination of pregnancy before the completion of 37 weeks of gestation, remains one of the most critical challenges in contemporary perinatal care. High neonatal mortality rates, along with frequent neurological, respiratory, and developmental complications, underscore the importance of identifying risk factors associated with preterm labor. The aim of this review was to comprehensively synthesize current scientific evidence on the multifactorial etiology of preterm birth, encompassing biological, immunological, genetic, environmental, and socio-economic determinants. A systematic literature search was conducted in PubMed during January and February 2025, covering peer-reviewed publications from 2020 to 2024. Included in the analysis were meta-analyses, cohort studies, case-control studies, systematic reviews, and population-based analyses. The findings indicate a significant association between preterm birth and obstetric abnormalities, maternal comorbidities, inflammatory and genetic factors, as well as low socioeconomic status and limited access to prenatal care. In high-income countries, assisted reproductive technologies (ART), particularly fresh embryo transfer, continue to pose a considerable risk. The conclusions emphasize the need for an interdisciplinary approach to prevention, standardization of diagnostic criteria, and further development of biomarker-based tools and personalized strategies for perinatal care.